Back to the forest: Exploring forest transitions in Candelaria Loxicha, Mexico - Aguilar-Støen, M.; Angelsen, A.; Moe, S.R. (2011)
Declining proi tability of agriculture and/or higher prices of forest products and services typically drive an increase in forest cover. This article examines changes in forest cover in Candelaria Loxicha, Mexico. Forest cover increased in the area as a result of coffee cultivation in coffee forest-garden systems. Dependence on forest products and services, and not prices of forest products, drive the process in our study site. Low international coffee prices and high labor demand outside the community might pull farmers out of agriculture, but they do not completely abandon the lands. A diversii cation in income sources prevents land abandonment and contributes to maintaining rural populations and coffee forest gardens